Improving Student Motivation and Learning Outcomes Through the Application of Problem-Based Learning Models in Mathematics Learning Specialization - Simson, Simson (Universitas Negeri Makassar, 2023)
Teachers as educational professionals have an important role in the teaching and learning process. Teachers must be able to explain their knowledge to their students through managing learning by applying teaching approaches and models that are appropriate to the subject matter and cognitive level of students. aims to improve the mathematics learning abilities of XI IPA 2 students at SMAN 7 Sigi even semester for the 2022/2023 academic year in the basic competence